Sistem Monitoring Serapan Anggaran Belanja Barang Dan Jasa, Menggunakan Metode Rapid Application Development (Rad) - Mufti Mutthohari, Aiddin; Sri Eniyati (Universitas Sari Mutiara Indonesia Medan, 2022)
The Police Academy is in the management of the budget absorption of goods and services, in each work unit and sub-unit under it has a budget absorption to support activities that take place at the Police Academy, from the planning sub-division which manages the budget absorption data at the Police Academy using an offline system where the data is not connected between the work unit staff and the Directorate of Administrative Planning (Bagrenmin) so it takes a long time. Submission of this thesis aims to develop a budget evaluation system at the Police Academy using a web-based application so that it can facilitate operators in processing financial data and facilitate managerial monitoring and evaluation. So that it makes it easier to manage budget absorption data within the Police Academy and shortens the time in processing it. Then the programming language used is php, the framework used is CodeIgniter and the data storage uses a mysql database. This study uses the RAD method in its application it does not take a lot of time so that it can shorten the time in making the system.